A8.17 The Role of CXCR2 Signalling in Articular Cartilage Homeostasis. (25th February 2013) - Sherwood, J; Bertrand, J; Nalesso, G; Achan, P; Pitzalis, C; Pap, T; Dell'Accio, F
Abstract : Background and Objectives: The production of ELR+ CXC chemokines is widely studied in arthritis and is thought to contribute to the inflammatory phenomena that lead to cartilage breakdown. Healthy articular chondrocytes however, also express their own chemokine receptors and ligands, however their function in these cells is puzzling because chondrocytes are encased in a dense extracellular matrix and are not known to migrate in vivo. This study aims to identify the function of this signalling mechanism in articular cartilage. Materials and Methods: Adult human articular chondrocytes were expanded in monolayer culture under standard conditions. CXCR1 and CXCR2 expression was confirmed using semiquantitative reverse transcription polymerase chain reaction (RT-PCR) and Western blotting. Chemokine receptors and ligands were detected in human articular cartilage from healthy and osteoarthritis patients and in mouse articular cartilage using immunohistochemistry. CXCR1/2 signalling was blocked at specific receptor level in human chondrocytes using validated blocking antibodies and siRNA. Chondrocyte phenotypic gene expression was assessed using real time RT-PCR. The content of highly sulphated proteoglycans in chondrocyte micromasses was analysed using Alcian blue staining, guanidine HCl extraction and spectrophotometric quantification. Surgical destabilisation of the medial meniscus (DMM) was used to induce instability into the left knees of 8 week old CXCR2 -/- mice and wild type BALB/C controls (N = 10 per group). Right knees were sham operated as control. 8 weeks following surgery, mice were culled, knee joints were paraffin embedded and sectioned. Representative sections were stained using Safranin orange and osteoarthritis severity was assessed by Chambers scoring. Results: ELR+ CXC chemokines and their receptors, CXCR1 and CXCR2 were expressed in normal human articular cartilage. CXCR1 and CXCR2 were expressed in articular cartilage from osteoarthritis patients, however their ligands, CXCL8 and CXCL6, were lost from the territorial matrix of chondrocytes. Blockade of CXCR1/2 signalling at receptor level in chondrocytes resulted in a significantly reduced extracellular matrix sulphated glycosaminoglycan content of micromass cultured chondrocytes and a significantly reduced expression of the chondrocyte differentiation markers COL2A1, Aggrecan and SOX9. CXCR2 and CXCL5 were expressed in unchallenged wild type mouse articular cartilage. CXCR2 -/- mice subjected to the DMM model and analysed 8 weeks following surgery developed a significantly more severe osteoarthritis phenotype than wild type controls. Conclusions: Our findings indicate that CXCR1/2 signalling is required for the maintenance of phenotypic stability of articular chondrocytes. We show that mouse CXCR2 signalling is required for articular cartilage homeostasis and is chondroprotective during conditions of challenge in vivo.